2022
DOI: 10.1002/ase.2241
|View full text |Cite
|
Sign up to set email alerts
|

Application of HoloLens‐based augmented reality and three‐dimensional printed anatomical tooth reference models in dental education

Abstract: Tooth anatomy is fundamental knowledge used in everyday dental practice to reconstruct the occlusal surface during cavity fillings. The main objective of this project was to evaluate the suitability of two types of anatomical tooth reference models used to support reconstruction of the occlusal anatomy of the teeth: (1) a three‐dimensional (3D)‐printed model and (2) a model displayed in augmented reality (AR) using Microsoft HoloLens. The secondary objective was to evaluate three aspects impacting the outcome:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
(171 reference statements)
0
5
0
Order By: Relevance
“… 22–25 For instance, some efforts to develop the students’ skills in replicating dental morphology implemented augmented reality, by providing virtual teeth models that is displayed in the real world by Microsoft Hololens, suggest that augmented reality can be helpful in dental anatomy education, but now they are still not suitable replacements for physical 3D models. 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22–25 For instance, some efforts to develop the students’ skills in replicating dental morphology implemented augmented reality, by providing virtual teeth models that is displayed in the real world by Microsoft Hololens, suggest that augmented reality can be helpful in dental anatomy education, but now they are still not suitable replacements for physical 3D models. 26 …”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] For instance, some efforts to develop the students' skills in replicating dental morphology implemented augmented reality, by providing virtual teeth models that is displayed in the real world by Microsoft Hololens, suggest that augmented reality can be helpful in dental anatomy education, but now they are still not suitable replacements for physical 3D models. 26 In the future we seek to upgrade our efforts to include developing the dental student's self-assessment skills of their dental carvings; it was reported that a statistically significant correlation exists between self-assessment ability and waxing performance in dental students. 27 Accordingly, we are establishing a website where students can upload photos of their carvings and use a special software designed by us to assess and compare their carvings to the correct anatomical sculptures desired from them (unpublished work).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, among advanced VR technologies, the use of mixed-reality technology using Microsoft’s HoloLens provides an augmented and virtual experience in dental education and is highly effective [ 43 , 44 ]; hence, it is a good alternative in DR learning. Nevertheless, educational and training institutions face significant financial challenges with regard to acquiring both equipment and content [ 45 , 46 ], making the provision of these resources to students challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 360° videos and pHMDs offer several advantages when used for the purpose of education in a nonface-to-face online environment. Furthermore, among advanced VR technologies, the use of mixed-reality technology using Microsoft's Holo-Lens provides an augmented and virtual experience in dental education and is highly effective [43,44]; hence, it is a good alternative in DR learning. Nevertheless, This photo shows that a 360° recorded video is played by dividing the same video into the left and right eyes on a smartphone attached to pHMD.…”
Section: Discussionmentioning
confidence: 99%
“…While studies with HoloLens can be found in numerous medical fields, there is a noticeable lack of extensive research within the dental field, especially with the latest version of HoloLens. Existing studies employing HoloLens for the study of dental applications can be grouped into two categories: focused on training [18,19] or monitoring [20,21] and interaction based [22]. The first one focuses on displaying virtual content, while the latter involves the interaction between virtual content and real objects, which is the category with which guided implant placement studies are associated.…”
Section: Related Workmentioning
confidence: 99%